Case report: Novel use of clinical brain-computer interfaces in recreation programming for an autistic adolescent with co-occurring attention deficit hyperactivity disorder - Van Damme, Susannah; Mumford, Leslie; Johnson, Aleah; Chau, Tom (Frontiers in Human Neuroscience, 2024)
In recent years, several autistic 1 children and youth have shown interest in Holland Bloorview Kids Rehabilitation Hospital's clinical brain computer interface (BCI) program. Existing literature about BCI use among autistic individuals has focused solely on cognitive skill development and remediation of challenging behaviours. To date, the benefits of recreational BCI programming with autistic children and youth have not been documented. Purpose: This case report summarizes the experiences of an autistic male adolescent with co-occurring attention deficit hyperactivity disorder using a BCI for recreation and considers possible benefits with this novel user population.Methods: A single retrospective chart review was completed with parental guardian's consent.The participant demonstrated enjoyment in BCI sessions and requested continued opportunities to engage in BCI programming. This enjoyment correlated with improved Canadian 1 Identity-first language is the preferred language of many, though not all, people in the autism community (Keating, et al., 2023). We use this language but recognize that individual preferences will vary and should be respected. Occupational Performance Measure (COPM) scores in BCI programming, outperforming scores from other recreational programs. Additionally, clinicians observed changes in social communication efforts and self-advocacy in this first autistic participant. Conclusion: The use of brain computer interfaces in recreational programming provides a novel opportunity for engagement for autistic children and youth that may also support skill development.